ANALISIS PELUANG DAN TANTANGAN PENGEMBANGAN HALAL TOURISM DALAM MENINGKATKAN PEREKONOMIAN INDONESIA DI ERA DISRUPSI - Kaysa Hasnah Mumtaaza; Zukhrufa Hizballah Tsania; Alya Arini Putri; Lina Marlina (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
The development of halal tourism in Indonesia holds significant potential to drive national economic growth, especially in the era of disruption characterized by rapid technological advancement, shifting consumer preferences, and dynamic global trends. This study aims to analyze the opportunities and challenges in developing the halal tourism sector as a strategic effort to enhance Indonesia's economic competitiveness. The research uses a descriptive qualitative approach, based on literature review and secondary data from official sources. The findings indicate that the opportunities for developing halal tourism include: the growing number of global Muslim travelers, supportive government regulations, and Indonesia's advantage as the country with the largest Muslim population in the world. However, several challenges remain, such as limited supporting infrastructure, uneven halal certification standards, low industry awareness of halal tourism concepts, and intensifying global competition. Therefore, a collaborative strategy between the government, industry stakeholders, and the community is essential to optimize halal tourism’s potential as a key driver of Indonesia’s economy in the disruptive era. This study is expected to contribute to policy formulation and sustainable tourism practices based on halal values.Keywords : halal tourism, Indonesian economy, disruptive era, opportunities, challenges, sustainable tourism